2010
DOI: 10.1080/03055698.2010.506330
|View full text |Cite
|
Sign up to set email alerts
|

Peer‐tutoring: what’s in it for the tutor?

Abstract: Drawing on role theory and socio-constructivist ideas about learning, this study explores how peer-tutoring can support tutors' learning. The sample comprised ten 16-17-year-old biology tutors, working with twenty-one 14-15-year-old students from a science class over eight weeks. Data were collected through an online wiki, tutor interviews, paired tutor discussions and video recordings. Tutors' perceptions of their role motivated them to learn the material, and their learning was supported by discussion and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 25 publications
3
47
0
2
Order By: Relevance
“…For example, students who taught their peers reported greater intrinsic motivation and higher self-efficacy beliefs than those who studied for their own learning (Benware and Deci 1984;Miller et al 2010). Also, student tutors showed better class participation (behavioral engagement), spent more time on conceptual understanding of the subject matter (cognitive engagement), and reported higher interest in the content (emotional engagement) (Arco-Tirado et al 2011;Benware and Deci 1984;Galbraith and Winterbottom 2011). This tutor learning effect is often referred to as learning-by-teaching (Gartner et al 1971).…”
Section: Theoretical Foundationsmentioning
confidence: 95%
“…For example, students who taught their peers reported greater intrinsic motivation and higher self-efficacy beliefs than those who studied for their own learning (Benware and Deci 1984;Miller et al 2010). Also, student tutors showed better class participation (behavioral engagement), spent more time on conceptual understanding of the subject matter (cognitive engagement), and reported higher interest in the content (emotional engagement) (Arco-Tirado et al 2011;Benware and Deci 1984;Galbraith and Winterbottom 2011). This tutor learning effect is often referred to as learning-by-teaching (Gartner et al 1971).…”
Section: Theoretical Foundationsmentioning
confidence: 95%
“…That is, through learning by teaching, individuals theoretically learn content more deeply by teaching it to others compared with learning the content just for oneself. However, the reasons for this positive effect on learning remain unclear (Fiorella & Mayer, 2013;Galbraith & Winterbottom, 2011;Peets et al, 2009;Rohrbeck, GinsburgBlock, Fantuzzo, & Miller, 2003;Roscoe & Chi, 2007), and some research has shown no positive effects (Renkl, 1995) or negative effects (Ehly, Keith, & Bratton, 1987) on learning. In their seminal article, Bargh and Schul (1980) proposed that the expectation of teaching content to others results in a change in the way individuals study that material compared with normal studying for oneself.…”
Section: Learning By Teachingmentioning
confidence: 99%
“…Four components of tutor's perceptions of tutoring have been investigated in the literature: their perceptions of their role as tutors and the purpose of tutoring (Colvin, 2007;Moore, 2009;Bailey, 2010;Galbraith and Winterbottom, 2011), characteristics of effective tutors (Jelfs et al, 2009;Xiao, 2012), characteristics of tutees (Bailey, 2010), and characteristics of effective tutoring (Wood et al, 1976;Topping, 1996;Lepper et al, 1997;Falchikov, 2001).…”
Section: Tutors' Perceptions Of Tutoringmentioning
confidence: 99%